2009
DOI: 10.1590/s0102-311x2009001500010
|View full text |Cite
|
Sign up to set email alerts
|

Association between stress and breast cancer in women: a meta-analysis

Abstract: The objective of the current meta-analysis was to verify the association between stressful life events and primary breast cancer incidence in women. A total of 618 studies from 1982-2007 were found in the PubMed, LILACS, and Cochrane Library databases. Methodological quality was evaluated according to the Downs & Black criteria. Eight studies were selected (six case-controls and two cohorts). The studies were grouped in three analyses, two of which based on the categories widowhood and divorce and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 70 publications
4
29
0
3
Order By: Relevance
“…accumulation of the individual life events and total life event scores, finding similar tendencies in breast cancer risk behaviors. Our results agree with the recent metaanalysis of Santos et al (2009) who found a statistically significant relationship between stressful life events of high intensity and breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…accumulation of the individual life events and total life event scores, finding similar tendencies in breast cancer risk behaviors. Our results agree with the recent metaanalysis of Santos et al (2009) who found a statistically significant relationship between stressful life events of high intensity and breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…There is another trend in Kazakhstan: adverse living conditions of lower social strata of population living in rural areas is a risk factor for development of BC, which is consistent with some recent publications (Nosheen Fatima et al, 2010;Das et al, 2012). Several studies mention the role and significance of such factors like abortion, hereditary predisposition, and chronic stress (Collaborative Group on Hormonal Factors in Breast Cancer, 2004;Santos et al, 2009;Amir et al, 2010;Antonova et al, 2011). Our observation confirms such findings-the abortion (OR=2.67), hereditary predisposition (OR=3.36), and chronic stress (OR=3.61) was more common in cases of breast cancer, but to a lesser extent compared to other identified risk factors.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, in their estimation a feeling of happiness and optimism significantly decreased BC risk (OR=0.75, 95%CI=0.64-0.86). In turn, Santos et al (2009) in their meta-analysis including the latter findings reported statistically significant increased BC risk among women who had reported experience of stressful life events of high intensity. In the recent Polish case-control study (858 cases, 1085 controls) women with four to six individual major life events had over 5-times higher risk for BC compared with those not reporting major life events experience (OR=5.33, 95%CI=4.01-8.21) (Kruk, 2012).…”
Section: Psychological Stressmentioning
confidence: 91%